The impact of financial position on investment: an anlysis for non-financial corporations in the euro area - Carmen Martinez-Carrascal; Annalisa Ferrando (European Central Bank (ECB), 2008)
This paper analyses the impact that firms financial position has on investment decisions using panel data from a large sample of non-financial corporations(around 120,000 firms) in six euro area countries(Belgium, Germany, France, Italy, the Netherlands and Spain). The results indicate that financial position is important to explain capital expenditures, as financial pressure appears relevant in explaining investment dynamics when it is proxied by cash flow, indebtedness and debt burden. The results also show dierences in the sensitivity of investment rates to changes in financial pressure across countries, which appears to be especially large in the Netherlands and Italy and relatively small in Germany.
Keywords: C33; E22; G32; J23; 330; balance sheet channel; Financial pressure; fixed investment; panel data; Investitionsentscheidung; Investitionspolitik; Unternehmensfinanzierung; Kapitalstruktur; Belgien; Deutschland; Frankreich; Italien; Niederlande; Spanien